A case report of resected ectopic malignant meningioma with lung metastasis - Murakami, Kotaro (Medicine (Baltimore), 2019)
INTRODUCTION: Meningioma is mostly a benign tumor, but sometimes it is malignant, and there have been reports of distant metastases. PATIENT CONCERNS: The patient, a woman in her 40s, was under follow-up after resection of an ectopic malignant meningioma originating in the left axilla. She was referred to our department because of a nodule shadow in the right lung on chest computed tomography (CT) 3 years and 5 months postoperatively. DIAGNOSIS: Chest CT showed a 1.0 cm nodule shadow in the right S4, which was positive on positron emission tomography-CT; no abnormality was found in any other organ. Therefore, it was considered to be a metastatic lung tumor. INTERVENTIONS: Right middle lobe partial resection was performed using thoracoscopic surgery, and a diagnosis of pulmonary metastasis of ectopic malignant meningioma was made by histopathology and immunohistochemistry. OUTCOMES: In this case, complete resection was possible. CONCLUSION: Meningioma occurs mainly in the cranium, and occurrence in the soft tissue of the extremities is extremely rare. To our knowledge, ours is the first report of a histologically malignant ectopic meningioma with metastasis to the thoracic cavity.